PENINGKATAN NILAI OVERALL EQUIPMENT EFFECTIVENESS PADA PROSES PEMBUATAN KACA CERMIN DENGAN METODE FMEA - Harun Al Rasyid (Universitas Mercu Buana, 2018)
PT. ABC as the manufacturer of the mirror trying to make improvements is effective in all production lines, the achievement of value of Overall Equipment Effectiveness (OEE) in the production department shows a very low OEE value. The main factors affecting the low value of the OEE is a factor of downtime, machine performance and high defect rate during the production process. Through analysis of the Six Big Losses obtained three factors, including the factor breakdown, reduce speed and quality losses. To identify losses and reduce the chances of system failure or process performed the analysis using FMEA method with the objective of determining the value of the highest RPN to priority improvements. The highest RPN value to the breakdown and quality was caused by the low quality of raw glass. While the highest RPN value to reduce speed due to the size factor process inefficient. Through the method of 5W+1H drawn up plans for corrective action to be deployed in production department. After doing the improvements for six months as recommended, the OEE value increased.